Cadmium accumulation and apoplastic and symplastic transport in Boehmeria nivea (L.) Gaudich on cadmium-contaminated soil with the addition of EDTA or NTA. Issue 59 (28th June 2015) - Yin, Yicheng; Wang, Yaqin; Liu, Yunguo; Zeng, Guangming; Hu, Xinjiang; Hu, Xi; Zhou, Lu; Guo, Yiming; Li, Jiang
<x xml:space="preserve">Abstract</x> A Cd-tolerant plant species named Boehmeria nivea (L.) Gaudich (ramie) was applied to study its Cd accumulation and translocation mechanisms with the addition of ethylene diamine tetracetic acid (EDTA) or nitrilotriacetic acid (NTA).